Odpowiedź :
a)(4p -3r)(p+2r)-(3p-r)(p+6r)=4p²+8pr-3pr-6r²-(3p²+18pr-pr-6r²)=4p²+5pr-6r²-3p²-18pr+pr+6r²=p²-12pr
b)4(2a-b)(2a+4b)-(3a-2b)(3b-2a)=4(4a²+8ab-2ab-8b²)-(9ab-6a²-6b²+4ab)=
16a²+12ab-8b²-13ab+6a²+6b²=22a²-ab-2b²
c)2d²-(3c-2d)(c-d)-c(c-2d)+2d²=2d²-(3c²-3cd-2cd+2d²)-c²+2cd=2d²-3c²+5cd-2d²-c²+2cd=-4c²+7cd
Prosze:))
b)4(2a-b)(2a+4b)-(3a-2b)(3b-2a)=4(4a²+8ab-2ab-8b²)-(9ab-6a²-6b²+4ab)=
16a²+12ab-8b²-13ab+6a²+6b²=22a²-ab-2b²
c)2d²-(3c-2d)(c-d)-c(c-2d)+2d²=2d²-(3c²-3cd-2cd+2d²)-c²+2cd=2d²-3c²+5cd-2d²-c²+2cd=-4c²+7cd
Prosze:))
(4p -3r)(p+2r) - (3p-r)(p+6r) = 4p² + 8pr - 3pr - 6r² - 3p² - 18pr + pr + 6r² = p² - 12pr
4(2a-b)(2a+4b)-(3a-2b)(3b-2a) = 4(4a² + 8ab - 2ab - 8b²) - (9ab - 6a² - 6b² + 4ab) = 16a² + 12ab - 8b² - 13ab + 6a² + 6b² = 22a² - ab - 2b²
2d²-(3c - 2d)(c-d)-c(c-2d)+2d²= 2d² - (3c² - 3cd - 2cd + 2d²) - c² + 2cd = 2d² - 3c² + 5cd - 2d² - c² + 2cd = -4c² + 7cd
:):)
4(2a-b)(2a+4b)-(3a-2b)(3b-2a) = 4(4a² + 8ab - 2ab - 8b²) - (9ab - 6a² - 6b² + 4ab) = 16a² + 12ab - 8b² - 13ab + 6a² + 6b² = 22a² - ab - 2b²
2d²-(3c - 2d)(c-d)-c(c-2d)+2d²= 2d² - (3c² - 3cd - 2cd + 2d²) - c² + 2cd = 2d² - 3c² + 5cd - 2d² - c² + 2cd = -4c² + 7cd
:):)